Medium Term Follow-Up of 337 Patients With Coronavirus Disease 2019 (COVID-19) in a Fangcang Shelter Hospital in Wuhan, China - Yan, Nao; Wang, Wei; Gao, Yongzhe; Zhou, Junhui; Ye, Jiuhong; Xu, Zhipeng; Cao, Jing; Zhang, Junjian (Frontiers in Medicine, 2020)
Background. With the adoption of powerful preventive and therapeutic measures, a large number of patients with COVID-19 have recovered and been discharged from hospitals in Wuhan, China. Prevention of epidemic rebound is a top priority of current works. However, information regarding post-discharge quarantine and surveillance of recovered patients with COVID-19 is scarce. Methods. This study followed up 337 patients with COVID-19 in Wuhan East-West Lake Fangcang shelter hospital during the post-discharge quarantine. Demographic, clinical characteristics, comorbidities, and chest computed tomography (CT) image, mental state, medication status, and nucleic acid test data were summarized and analyzed. Results. 21 (6.2%) patients were SARS-CoV-2 nucleic acid re-positive, and 4 (1.2%) patients were suspected positive. The median day interval between the discharge to nucleic acid re-positivity was 7.5 days (IQR, 6-13), ranging from 6 to 13 days. Cough/expectoration are the most common symptoms, followed by chest congestion/dyspnea during the two weeks post-discharge quarantine. Risk factors of nucleic acid re-positivity including the number of lobes infiltration (odds ratio[OR], 1.14; 95%CI, 1.09-1.19), distribution (OR, 0.16; 95%CI, 0.13-0.19), CT imaging feature of patchy shadowing accompanying with consolidation (OR, 9.36; 95%CI, 7.84-11.17), respiratory symptoms of cough accompanying with expectoration (OR, 1.39; 95%CI, 1.28-1.52), chest congestion accompanying with dyspnea (OR, 1.42; 95%CI, 1.28-1.57). Conclusion. The two weeks post-discharge quarantine may be an effective measure to prevent the outbreak from rebounding from the recovered patients. The second week is a critical period of post-discharge quarantine. Special attention should be paid to cough, expectoration, chest congestion, and dyspnea in recovered COVID-19 patients. A few recovered patients may prolong the quarantine based on clinical symptoms and signs and nucleic acid results in the two weeks of medical observation.